An uncommon side effect of a very commonly used medication: A case report on hydrocortisone-induced bradycardia - Alvin Oliver Payus; Ann Chee Chai; Norlaila Mustafa (John Wiley & Sons Ltd, 2021)
Sinus bradycardia is a rare but important side effect of high-dose hydrocortisone. It is a self-limiting condition that recovered spontaneously upon stopping the medication and did not recur with other types of corticosteroids.